EVALUATION OF PRE-WAR INCLUSIVE DEVELOPMENT BY INDICATORS OF EMPLOYMENT AND UNEMPLOYMENT IN UKRAINE - ZAVGORODNIY, Konstantin; NEIMET, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Employment and unemployment indicators determine the components of the inclusive development of the national economy. Ukraine’s aging population affects the workforce’s productivity and increases healthcare costs. In addition, the aging of the urban population affects the development of urban infrastructure and social services, particularly the demand for housing, transport, and cultural and entertainment services. On the other hand, if the population is younger, it can contribute to the development of innovations and technologies and increase the country’s economic potential. The young population can be more active and innovative, which helps support inclusive development in various sectors. Therefore, considering the population’s distribution by gender and age can help to understand what social and economic problems may arise and how they can be solved to achieve inclusive development. That is why the assessment of pre-war inclusive development by employment and unemployment indicators in Ukraine is quite relevant. The article aims to evaluate pre-war inclusive development based on indicators of employment and unemployment in Ukraine. Based on the results of the analysis for the years 2019-2021, the following conclusions were drawn. There is a specific improvement in the distribution of incomes in Ukraine: the share of the population with the lowest incomes is decreasing, and the share of the population with incomes from UAH 6,000 to UAH 11,000 is increasing; the most significant percentage of the population (24.7%) still receives the lowest incomes, which may indicate the need for further social support and encouragement to increase incomes in this population group; the ratio of total incomes of the most and least well-off 20% of the population does not change, which indicates that the improvement in income distribution does not occur due to the reduction of inequality between the more and less well-off strata of the population. The evaluation analysis showed that Ukraine’s labor force is decreasing yearly; from 2019 to 2021, it decreased by 744,400 people. It was determined that the level of participation of the population in the labor force decreases every year, which indicates that fewer and fewer people between the ages of 15 and 70 are willing and able to work. Accordingly, the level of employment also decreases. In particular, the decrease in employment occurs mainly among people of working age. It was emphasized that unemployment is increasing among people aged 15 to 70 and those of working age.